Testing the 'Extreme Female Brain' Theory of Psychosis in Adults with Autism Spectrum Disorder with or without Co-Morbid Psychosis. - Felicity V Larson; Meng-Chuan Lai; Adam P Wagner; MRC AIMS Consortium; Simon Baron-Cohen; Anthony J Holland (PLoS ONE)
Introduction Males and females in the general population differ, on average, in their drive for empathizing (higher in females) and systemizing (higher in males). People with autism spectrum disorder (ASD) show a drive for systemizing over empathizing, irrespective of sex, which led to the conceptualisation of ASD as an 'extreme of the typical male brain'. The opposite cognitive profile, an 'extreme of the typical female brain', has been proposed to be linked to conditions such as psychosis and mania/hypomania. Methods We compared an empathizing-over-systemizing bias (for short 'empathizing bias') in individuals with ASD, who had experienced psychotic illness (N = 64) and who had not (N = 71). Results There were overall differences in the distribution of cognitive style. Adults with ASD who had experienced psychosis were more likely to show an empathizing bias than adults with ASD who had no history of psychosis. This was modulated by IQ, and the group-difference was driven mainly by individuals with above-average IQ. In women with ASD and psychosis, the link between mania/hypomania and an empathizing bias was greater than in men with ASD. Conclusions The bias for empathizing over systemizing may be linked to the presence of psychosis in people with ASD. Further research is needed in a variety of clinical populations, to understand the role an empathizing bias may play in the development and manifestation of mental illness.